High-sensitive dual-band sensor based on microsize circular ring complementary terahertz metamaterial. Issue 1 (2nd January 2017) - He, Xunjun; Li, Shaopeng; Yang, Xingyu; Shi, Shuang; Wu, Fengmin; Jiang, Jiuxing
Abstract: Recently, resonance sensing based on the terahertz metamaterials has attracted considerable attentions due to the enhancement and confinement of local fields in microsize gap of resonant structures. Here, a high-sensitive dual-band sensor based on the complementary terahertz metamaterial composed of microsize circular ring gap array is proposed to detect the thickness and refractive index of thin film. The structure of this sensor is polarization insensitive dual-band operating mode and can be easily filled by the biomolecules. Simulation results demonstrate that the dual-band resonances are very sensitive to the dielectric variation, and the sensitivity levels of 99 GHz/refractive index unit (RIU) for mode f 1 and 242 GHz/RIU for mode f 2 are obtained and further enhanced by optimizing structures. Therefore, this structure can exhibit promising application for monitoring thin film thickness.